Fixed Point Theorem in \(G\)-Metric Space for Auxiliary Functions - Bhardwaj, Preeti; Kumar, Manoj (Communications in Mathematics and Applications, 2021)
In this paper, fixed point results satisfying generalized contractive condition with new auxiliary functions are proved in \(G\)-metric spaces.
Keywords: fixed point; auxiliary functions; G-metric space